Traditional Beliefs and Practices Among Pregnant Women In Javanese Communities: A Systematic Review - Salshabiyla Naura Almamira Cukarso; Chahya Kharin Herbawani (Journal of Public Health Research and Community Health Development, 2020)
Background: The Javanese community is one of the largest ethnic groups in Indonesia. This culture influences people's behaviour in daily life, including maternal care. Some people still believe in traditional myths and practices related to pregnancy. Even it can threaten the pregnancy. Purpose: This systematic review aims to describe the behaviour of people related to practices and beliefs in Javanese culture. Method: This review used a systematic review method. A systematic and relevant search for scientific articles through Google Scholar with a publication period between 2010-2020. Result: There are still many people who obey  the traditional beliefss that has no scientific basis. They hope by believing this can make the pregnancy run smoothly and avoid unwanted events. Conclusion: Traditional beliefs and practices have positive and negative impacts on pregnant women. Health workers must provide evidence-based interventions or health education about pregnancy to the community to prevent behaviour that is contrary to health values and can be harmful to the mother and fetus. Information about pregnancy care is not only conveyed to pregnant women but can also be shared with her husband or parents.